A Novel FLCN Intragenic Deletion Identified by NGS in a BHDS Family and Literature Review - Cai, Minghui; Zhang, Xinxin; Fan, Lizhen; Cheng, Shuwen; Kiram, Abdukahar; Cen, Shaoqin; Chen, Baofu; Ye, Minhua; Gao, Qian; Zhu, Chengchu; Yi, Long; Ma, Dehua (Frontiers in Genetics, 2021)
Birt-Hogg-Dubé syndrome (BHDS，MIM #135150), caused by germline mutations of FLCN gene, is a rare autosomal dominant inherited disorder characterized by skin fibrofolliculomas, renal cancer, pulmonary cysts and spontaneous pneumothorax. The syndrome is considered to be under-diagnosed due to variable and atypical manifestations. Herein we present a BHDS family. Targeted next generation sequencing (NGS) and multiplex ligation-dependent probe amplification (MLPA) revealed a novel FLCN intragenic deletion spanning exons 10-14 in four members including the proband with pulmonary cysts and spontaneous pneumothorax, one member with suspicious skin lesions and a few pulmonary cysts, as well as two asymptomatic family members. In addition, a linkage analysis further demonstrated one member with pulmonary bullae to be a BHDS-ruled-out case, whose bullae presented more likely as an aspect of paraseptal emphysema. Furthermore, the targeted NGS and MLPA data including our previous and present findings were reviewed and analyzed to compare the advantages and disadvantages of the two methods, and a brief review of the relevant literature is included. Considering the capability of the targeted NGS method to detect large intragenic deletions as well as determining deletion junctions, and the occasional false positives of MLPA, we highly recommended targeted NGS to be used for clinical molecular diagnosis in suspected BHDS patients.